Pliometría en el tratamiento fisioterapéutico post distensión grado II, ligamento colateral medial de la rodilla - Cristina Estefanía, Calderón González (2021)
The knee medial collateral ligament strain occurs with a higher incidence in people who practice high-impact activities. Although the treatment of ligamentous injuries has improved in recent decades, it is known that the healing ability of a torn ligament depends on several factors, including anatomical location, presence of associated injuries, and selected treatment modality. Plyometrics increase strength and explosiveness through muscle contractions taking advantage of elastic energy to perform maximum tension at short intervals of time. The research design was a documentary and bibliographic review about the plyometry technique in grade II distension of the knee medial collateral ligament. It was carried out in scientific databases: Scielo, Scopus, Pubmed, Academia, Medline, Embase, PEDro, Lilacs. The search focused on intervention studies and randomized trials. They were about 140 articles found but the duplicate files were eliminated; titles and abstracts were examined. The quality of the methodology was assessed using the Physiotherapy Evidence Database scale, leaving 50 articles for exhaustive analysis that contributed to the research. The analyzed results conclude that plyometric training is a tool for the prevention and management of injuries, positively affecting muscle strength, bone health, body composition, postural stability, jumping and performance: It provides a variety of neuromuscular and impact stimuli. In a nutshell, the stiffness of various elastic components of the muscle-tendon and muscle-ligament complex of the lower limb change; therefore, a plyometric program increases neuronal efficiency, correcting proprioceptive and neuromuscular deficits.